A Semi-Systematic Review on High Reliability Organizational – The Top Areas of Research Interest - Karolina Wielicka-Ganczarczyk (Communications of International Proceedings, 2021)
Nearly 20 years ago, Weick and Sutcliffe presented five characteristics that describe HRO. Subsequently, most academic publications on HRO have referred to these characteristics defined by Weick and Sutcliffe [1]. Initially, the term HRO concerned organizations that operate in challenging, complex environments and can cause catastrophic damage to themselves and the wider community. Research has mainly focused on three types of companies, i.e., nuclear power plants, airlines, air traffic controls and aircraft carriers [2], and fire departments [3]. In this paper, a semi-systematic review was used to organize the research output in HRO and identify the current research trends in this area. For the adopted objective, three supporting research questions were posed related to the subject and object of study and the research methods used to investigate the problem. The study was based on two scientific articles databases, i.e., Scopus and Web of Science, in which 1,284 works on HRO were identified.
Keywords: High Reliability Organizations; HRO; Literature Review; Research Areas.